CRITICAL THINKING SKILLS IN INTEGRATED SCIENCE LEARNING VIEWED FROM LEARNING MOTIVATION - Cholisoh, L.; Fatimah, S.; Yuniasih, F. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
The study aimed to determine the effect of Predict Discuss Explain Observe Discuss Explain and Small Group Discussion strategies toward critical thinking skills and the influence of learning motivation toward critical thinking skills. This study was a quasi experiment with the non-equivalent pretest-posttest design. Data were analysed by inferential statistics of two way analysis of variance and regression analysis. The results showed that Predict Discuss Explain Observe Discuss Explain and Small Group Discussion strategies were influential toward critical thinking skills and the average of students critical thinking skills using Small Group Discussion strategy was better than those experiencing Predict Discuss Explain Observe Discuss Explain strategy. Furthermore, learning motivation were also influential toward critical thinking skills. Students having high learning motivation were better than students having low learning motivation. Regression analysis showed learning motivation and critical thinking skills have positive correlation. Influence of learning motivation toward critical thinking skill was about 6.4%.Penelitian ini bertujuan untuk mengetahui pengaruh strategi Predict Discuss Explain Observe Discuss Explain dan Small Group Discussion terhadap kemampuan berpikir kritis, dan pengaruh motivasi belajar terhadap kemampuan berpikir kritis. Penelitian ini merupakan penelitian quasi experiment menggunakan desain the non-equivalent pretest-posttest. Data dianalisis menggunakan statistik inferensial Analisi Varian dua jalur dan analisis regresi. Hasil penelitian menunjukkan bahwa strategi Predict Discuss Explain Observe Discuss Explain dan Small Group Discussion berpengaruh terhadap kemampuan berpikir kritis, rata-rata kemampuan berpikir krtis siswa yang menggunakan strategi Small Group Discussion lebih baik daripada siswa yang menggunakan strategi Predict Discuss Explain Observe Discuss Explain. Selain itu, motivasi belajar berpengaruh terhadap kemampuan berpikir kritis. Rata-rata kemampuan berpikir kritis siswa yang mempunyai motivasi belajar tinggi lebih baik daripada siswa yang mempunyai motivasi belajar rendah. Berdasarkan analisis regresi, motivasi belajar dan kemampuan berpikir kritis memiliki hubungan yang positif. Motivasi belajar memberikan pengaruh sebesar 6,4% terhadap kemampuan berpikir kritis.